2011
DOI: 10.1142/s1088424611003641
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenzodiazaporphyrin: the semiconducting hybrid of phthalocyanine and tetrabenzoporphyrin

Abstract: Bicyclo[2.2.2]octadiene(BCOD)-fused diazaporphyrin was synthesized by the reaction of BCOD-fused dipyrromethane with sodium nitrite in acetic acid/ethanol in the presence of copper(II) acetylacetonate. This soluble precursor was converted into the semiconducting thin film of (tetrabenzodiazaporphyrinato)copper(II) by heating after fabrication via spin-coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These solution-processed devices have attained power conversion efficiencies as high as 5%, and the performance of TBP-based PV cells could be improved by introducing different fullerenes. [93][94][95][96][97][98] To finish, a range of authors have established 99-102 some structure-property relationships depending on the specific field of application, but there are no simple rules for a specific response to each kind of use.…”
Section: Main Applications In Chemistry Catalysis Medical Diagnostics...mentioning
confidence: 99%
“…These solution-processed devices have attained power conversion efficiencies as high as 5%, and the performance of TBP-based PV cells could be improved by introducing different fullerenes. [93][94][95][96][97][98] To finish, a range of authors have established 99-102 some structure-property relationships depending on the specific field of application, but there are no simple rules for a specific response to each kind of use.…”
Section: Main Applications In Chemistry Catalysis Medical Diagnostics...mentioning
confidence: 99%
“…DAPs have received continuing interest in relation to their analogues, porphyrins and phthalocyanines. ,,, It has been shown that 5,15-aza-substitution significantly changes the intrinsic properties of the porphyrin π systems that would be comparable to or even better than their analogues. Nevertheless, due to synthetic difficulties of the cyclization and peripheral modification of the core in DAPs, the opportunity of using DAPs as materials has poorly been addressed. As such, DAPs have yet to be used as donors in D–A linked systems to elucidate the intrinsic ET properties.…”
Section: Introductionmentioning
confidence: 99%
“…66 More recently, Okujima et al reported a different type of copper-templated cyclization for a 2,3,7,8-substituted dipyrromethane using copper(II) acetylacetonate [Cu(acac) 2 ], sodium nitrite, and acetic acid, although the isolated yield of CuDAP 64 was low (Scheme 32). 132 Several meso-substituted and β-unsubstituted MDAPs 66 (M = Ni, Cu) 133,134 have been prepared in recent years by the metal-templated cyclization of the corresponding β-unsubstituted bis(1,9-dibromo-5-mesityldipyrrin) complexes 65-Br (M = Ni, Cu) according to Johnson's protocol (Scheme 33). 134 Interestingly, the distribution of cyclized products and their yields vary considerably depending on the nature of the reagents and reaction conditions.…”
Section: Chemical Reviewsmentioning
confidence: 99%